Micropropagation of Origanum acutidens (HAND.-MAZZ.) IETSWAART Using Stem Node Explants. (24th July 2013) - Yildirim, Mehmet Ugur
Abstract : Origanum acutidens (HAND.-MAZZ.) IETSWAART is a promising ornamental plant that can be widely used in landscape management. It is endemic to Eastern Anatolian region of Turkey. Tissue culture has not been used to micropropagate it. The study reports stem node explants from one-week-old seedlings of the plant for successful micropropagation. The stem nodes were cultured on MS medium containing 0.6, 1.2, 1.8, and 2.4 mg/L BAP with 0.2 mg/L NAA. Visible effects of culture media on shoot proliferation were recorded. Shoot regeneration rate was maximum on MS medium containing 1.80 mg/L BAP-0.2 mg/L NAA. The micropropagated shoots were rooted on MS medium containing 0.2 mg/L NAA. All microrooted plantlets survived during acclimatisation on peat moss. It was concluded that O. acutidens can be successfully micropropagated under in vitro conditions.